INFRASTRUKTUR DAN TEKNOLOGI DORONG KEMAJUAN UMKM - Ketut Rendi Astuti (Forum Manajemen, 2019)
Information technology has changed the lifestyle. The world has changed quickly and human behavior also has changed.Indonesia as a country with a very dense population of 4.0 industrial movements must certainly be observed wisely. Especially in regions that still prioritize local wisdom on a strong cultural basis.There is often a contradiction in the movement of technology which has the movement effect of lifestyle toward modernity. The construction of physical infrastructure to expedite goods and services and telecommunications network infrastructure, especially internet, is one of the keys to spur of economic growth.The incessant development of major infrastructure to remote rural areas is expected to spur the rate of distribution of goods and services throughout the country. The development of Micro Small And Medium Enterprises products compulsively have the government’s and all parties’ attention, in the form of regulations and policies.Therefore, Micro Small And Medium Enterprises can grow conducively and play a role in various economic sectors. It will be very fantastic if the development of Micro Small And Medium Enterprises products is also balanced with the pace of cyberspace infrastructure networks development.Various products in remote areas will be accelerated its marketing and distribution, even throughout the world. New startups will appear, grow and develop not only become unicorns, but also becomeDecacorns.The new startups are expected to build and develop a business network so that the industrial revolution 4.0 does not have an impact on termination of employment relationship. The industrial revolution 4.0 actually rises up Indonesia to become the owner of the largest and the biggest unicorn in the world.